SOLE PATTERNS IN SOME ETHNIC GROUPS - Chadikovska, Elizabeta; Zafirova, Biljana; Matveeva, Niki; Dodevski, Ace; Trpkovska, Biljana; Bojadzieva, Biljana (Journal of Morphological Sciences, 2021)
Populational dermatoglyphic study has been conducted in order to gain and compare data between different ethnic groups.The aims of the study is to establish analyze and compare individual dermatoglyphic features in healthy examinees of Macedonians, Albanians and Roma ethnic origin. In the current study some dermatoglyphic parameters were read on the right and left sole prints obtained from healthy individuals of Macedonian, Albanian and Roma ethnic origin.In each group sole prints were obtained from 100 males and 100 females. Sole prints were taken using Cummins and Midlo's ink method. Dermathoglyphics was classified and comparisment was made with results from other authors. We have found that most present patterns are found in the hallucal, first interdigital and distal thenar area on the sole, for both sexes. Second one according presence of the patterns is third interdigital area, with higher values in males compared to females, roma females with lowest values. Next is second interdigital configurational area on the sole, again higher pattern presence in males than females. Distal loops are most abundant pattern, followed by concentric whorls, rest of the patterns are present in lower percentage, for all groups and both sexes. For the present triradii the results are: d, c>b, a>pm>p>e>p’, p’’ in males and d>c>a, b>pm>p>e>p’>p’’ in females. The results, presented together with data on other dermatoglyphic features elaborated with other authors can serve as the basis of the dermatoglyphic status in healthy population with Macedonian, Albanian and Roma ethnic origin. They can also serve in further medico-biological investigation with theoretical and scientific purposes. Keywords : dermatoglyphics, sole prints, ethnic groups. https://doi.org/10.55302/JMS2141156ch